Reluctant regulators : how the West created and how China survived the global financial crisis - Goodstadt, Leo F. (Hong Kong University Press, 2011)
This book is a scathing indictment of regulatory inertia in the West. It provides important and original insights into the causes of financial crises and pays special attention to China's attempts at reform and Hong Kong's place in China's financial modernisation.